Hybrid Movements, Digital Technology, and the Rise and Fall of Far-Right Islamist Protest Mobilization in Indonesia - Salma, Aqida Nuril (Universitas Islam Internasional Indonesia (UIII), 2024)
What explains the rise and fall of far-right Islamist protest mobilization in contemporary Indonesia? The 2016-2017 Jakarta gubernatorial election witnessed significant growth in support for and mobilization of the far-right. While far-right Islamist mobilization has occurred regularly since the fall of the authoritarian Suharto regime in 1998, its longevity and impact on electoral politics has historically been limited. I maintain that the 2016 far-right Islamist protest mobilization was enabled and disabled by the dynamic relationship between hybrid media and hybrid movement strategies. Hybrid thinking serves as a platform for understanding the increasingly diverse and complex nature of Islamist mobilization, generating new ways of exploring some of the classic concerns of social movement studies and technology. Moreover, previous research on the far-right primarily focuses on electoral and party politics, while studies on social movements and technologies often fall into technological determinism, providing only a limited understanding of one of the most pressing issues of our time. This study proposes an innovative analytic strategy to understand the complexity of contemporary Islamist protest mobilization, creating a hybrid movement that effectively spans different movements, constituencies, and institutions, all coexisting within a hybrid media environment that deftly merges elements of old and newer media logics to influence participation, collaboration, and coordination in the spheres of social movements and protest politics.